Narrowing Interests: North American Adult Educators’ Discussions on Internationalization in the 1960’s - Catherine A Hansman; Amy D Rose (Adult Education Research Conference, 2018)
In examining the history of the field of Adult Education, interesting questions about the development of the knowledge base emerges. This research examines the countervailing strands and how the resulting focus narrowed the field to North America interests in the 1960’s.
Keywords: CPAE; Adult Education History; Academic field development